Enhanced Thermal Conductivity of Polyamide-Based Nanocomposites Containing Graphene Oxide Sheets Decorated with Compatible Polymer Brushes - Łątka, Łukasz (Materials (Basel), 2021)
Polyamide-based nanocomposites containing graphene platelets decorated with poly(acrylamide) brushes were prepared and characterized. The brushes were grafted from the surface of graphene oxide (GO), a thermally conductive additive, using atom transfer radical polymerization, which led to the formation of the platelets coated with covalently tethered polymer layers (GO_PAAM), accounting for ca. 31% of the total mass. Polyamide-6 (PA6) nanocomposites containing 1% of GO_PAAM were formed by extrusion followed by injection molding. The thermal conductivity of the nanocomposite was 54% higher than that of PA6 even for such a low content of GO. The result was assigned to strong interfacial interactions between the brushes and PA6 matrix related to hydrogen bonding. Control nanocomposites containing similarly prepared GO decorated with other polymer brushes that are not able to form hydrogen bonds with PA6 revealed no enhancement of the conductivity. Importantly, the nanocomposite containing GO_PAAM also demonstrated larger tensile strength without deteriorating the elongation at break value, which was significantly decreased for the other coated platelets. The proposed approach enhances the interfacial interactions thanks to the covalent tethering of dense polymer brushes on 2D fillers and may be used to improve thermal properties of other polymer-based nanocomposites with simultaneous enhancement of their mechanical properties.